2021
DOI: 10.47093/2713-069x.2021.2.1.59-62
|View full text |Cite
|
Sign up to set email alerts
|

Causes of death in patients with tuberculosis and human immunodeficiency virus co-infection

Abstract: Objectives. The aim of the study was to investigate the cause of death of tuberculosis patients infected with the human immunodeficiency virus (HIV). Many researchers and experts note the urgency of the problem of tuberculosis combined with HIV infection in the world and in Russia. One of the main criteria for assessing the effectiveness of medical care for tuberculosis patients infected with the human immunodeficiency virus is the mortality rate.Materials and methods. For a detailed study of the causes of dea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 2 publications
0
2
0
Order By: Relevance
“…Thus, among patients with coinfection, a widespread process or destruction in the lungs occurred in 78.6% of cases, while in patients with TB without HIV, it was only in 41.6% [9]. However, an earlier study on the causes of death in a group of HIV-TB patients [20] in five regions of the Russian Federation revealed that a lethal outcome was not associated only with TB in half of the cases. The most frequent causes of death include several secondary infections with wasting syndrome (ICD-10 codes: B20.7 and B22.2) in 19.7% of cases; other secondary infections-in 27.1%; cirrhosis of the liver developed as a result of hepatitis C or alcoholism-in 18.7%; drug overdose-in 12.3%; accidents-in 4.6% [20].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, among patients with coinfection, a widespread process or destruction in the lungs occurred in 78.6% of cases, while in patients with TB without HIV, it was only in 41.6% [9]. However, an earlier study on the causes of death in a group of HIV-TB patients [20] in five regions of the Russian Federation revealed that a lethal outcome was not associated only with TB in half of the cases. The most frequent causes of death include several secondary infections with wasting syndrome (ICD-10 codes: B20.7 and B22.2) in 19.7% of cases; other secondary infections-in 27.1%; cirrhosis of the liver developed as a result of hepatitis C or alcoholism-in 18.7%; drug overdose-in 12.3%; accidents-in 4.6% [20].…”
Section: Discussionmentioning
confidence: 99%
“…The currently existing system of prevention, including, first of all, preventive examinations and routine X-ray diagnostics, carried out at a certain time interval, is effective in patients with slowly developing TB without HIV (detection in 62.0%, at an early stage without lung destruction, 58.4%) [11], but for HIV-TB patients it is almost ineffective since it does not take into account the more rapid progression of TB in immunodeficient conditions [19,20] (in 78.6% of cases, there is already widespread process with destruction and dissemination). It is noted that changes in the X-ray pattern in miliary TB appear later than their clinical manifestations in immunodeficiency conditions [28].…”
Section: Discussionmentioning
confidence: 99%